2017
DOI: 10.4269/ajtmh.16-0842
|View full text |Cite
|
Sign up to set email alerts
|

Bites by the Monocled Cobra, Naja kaouthia, in Chittagong Division, Bangladesh: Epidemiology, Clinical Features of Envenoming and Management of 70 Identified Cases

Abstract: We describe 70 cases of monocled cobra (Naja kaouthia) bite admitted to Chittagong Medical College Hospital, Bangladesh. The biting snakes were identified by examining the dead snake and/or detecting N. kaouthia venom antigens in patients' serum. Bites were most common in the early morning and evening during the monsoon (May–July). Ligatures were routinely applied to the bitten limb before admission. Thirty-seven patients consulted traditional healers, most of whom made incisions around the bite site. Fifty-ei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(29 citation statements)
references
References 29 publications
0
28
0
1
Order By: Relevance
“…The degree of snakebite severity is also mediated by other factors, including the amount of venom that is injected, the route and anatomical site of injection, and the physiological and anatomical characteristics of the victim ( Gutiérrez, 2010 ). For example, Faiz et al (2017) found that the severity of neurotoxicity in the monocled cobra Naja kauthia envenomation is dependent on the amount of venom antigen in the circulation; a similar relation was observed in snakebites by Bothrops lanceolatus in Martinique ( Bucher et al, 1997 ). In children, bites tend to be more complicated than in adults, presumably due to their lower body mass and the faster absorption ( De Franco-Montalván et al, 1983 ).…”
Section: Discussionmentioning
confidence: 69%
“…The degree of snakebite severity is also mediated by other factors, including the amount of venom that is injected, the route and anatomical site of injection, and the physiological and anatomical characteristics of the victim ( Gutiérrez, 2010 ). For example, Faiz et al (2017) found that the severity of neurotoxicity in the monocled cobra Naja kauthia envenomation is dependent on the amount of venom antigen in the circulation; a similar relation was observed in snakebites by Bothrops lanceolatus in Martinique ( Bucher et al, 1997 ). In children, bites tend to be more complicated than in adults, presumably due to their lower body mass and the faster absorption ( De Franco-Montalván et al, 1983 ).…”
Section: Discussionmentioning
confidence: 69%
“…Most cases of cobra envenoming will develop local necrosis [24,51,52]. Although this pathological effect is not life threating, it usually leads to an irreversible outcome for snakebite victims.…”
Section: Discussionmentioning
confidence: 99%
“…Mortality and morbidity due to venomous snake bites are a great public health burden in Bangladesh, especially in rural areas. Bites from cobra snakes, including N. kaouthia and N. naja, are one of the leading causes of venomous snake envenomation in Bangladesh [47,48]. Syndromic approaches, not ELISA, are the main diagnostic methods due to the abundance of venomous snakes, including pit vipers, cobras, and kraits, which are variably distributed in Bangladesh [47,48].…”
Section: Discussionmentioning
confidence: 99%